PERAN KOMPETENSI DAN MODEL PENGORGANISASIAN DEWAN PENGAWAS SYARIAH TERHADAP PEMBIAYAAN BERBASIS BAGI HASIL PADA PERBANKAN SYARIAH DI INDONESIA - USAMAH USAMAH (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2010)
The purpose of this study is to analyze the influence of competence and organizational models Sharia Supervisory Board of profit and loss sharing financing in Islamic banking in Indonesia. The analysis in this study using the variables: scientific background, multiple positions, number of the day organizing and the supervision model of the DPS for profit and loss sharing financing. The sample used was secondary data from Sharia Banks (BUS) and Business Unit Sharia Banks (UUSBU) and his DPS obtained from Bank Indonesia (BI) is the form of Annual Report BUS / UUS from 2006 until the year 2008. Sample selection method used was purposive sampling and the sample selection criteria. Samples are used as much as 3 and 7 UUS BUS. This research statistical methods using Multiple Linear Regression Analysis, with a statistical test of hypothesis testing and statistical test t F. The results of F test analysis showed all the independent variables of scientific backgrounds, multiple positions, the number of days supervision and control model jointly affect the adherence of shariabased financing for the results The results of t test analysis showed that two variables scientific background variables and control models are not significant. For the results of t test analysis of the double variable positions and the number of days is a significant oversight